Fluency in distance learning - Fenton, Celeste; Watkins, Brenda Ward (Emerald Publishing Limited : Information Age Publishing, 2010)
Fluency in Distance Learning offers a practical, hands-on, workshop style approach to creating an effective distance learning course. Full of specific ideas and strategies, the authors guide you through the process from beginning to end. Specific instructions are provided for setting up a course home page, developing interactive content, and utilizing a variety of multimedia resources.Fluency in Distance Learning distinguishes itself from other publications on distance learning with its straightforward, practical workshop format. Specific strategies and examples of effective distance learning course materials help instructors to build a quality distance learning course quickly and effectively regardless of the learning management system being used. A companion website contains multimedia files and interactive exercises to enhance the reader's learning and understanding of distance learning pedagogy and content development for online courses. In addition, all the necessary media files for trainers to deliver a series of professional development workshops on distance learning, are also available.